Evaluating the role of market based policy instruments in managing trade-offs between ecosystem services supply and human welfare: case of Uluguru water catchment, Tanzania - Mungatana, Eric D. (University of Pretoria, 2017)
Thesis (PhD)--University of Pretoria, 2017.